The Effect of Additional Employee Income and Work Environment on The Performance of Civil Servants through Work Motivation - Siti Narmita Yamin; Idrus Taba; Andi Aswan (Magister Management, Hasanuddin University, 2021)
This study aims to find out the influence of the additional employee income and the work environment on the performance of civil servants through work motivation in the Regional Secretariat of Gowa District. Data collection is carried out by civil servants assigned in the Secretariat Office of Gowa District. Of 127 population, as many as 96 respondents are taken using the Slovin technique. On the basis of findings, the results showed that the additional employee income and the work environment have a positive and significant effect on work motivation. Further, the additional employee income and the work environment have a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Interestingly, work motivation is unable to mediate the relationship between additional employee income and employee performance. However, the work motivation can mediate the relationship between the work environment and the employee performance at the Gowa District Secretariat Office.